Influence of spatial variability on rock slope reliability using 1-D random fields - Pantelidis, Lysandros; Gravanis, Elias; Griffiths, D.V. (My University, 2015)
In this work, the theory of random fields is used to account for the influence of spatial variability on slope reliability. Within this framework the friction coefficient along a discontinuity is treated as a Gaussian random field which is fully described by its mean value, standard deviation and spatial correlation length. The random field is simulated using the Local Average Subdivision (LAS) method. As shown by the examples presented herein, the spatial correlation of shear strength along a failure plane can have an important influence on slope performance, as expressed by the failure probability. This is a significant observation since ignoring the influence of spatial correlation in design may lead to non-conservative estimations of slope reliability. The planar mode of failure is considered.
Keywords: Random fields; Rock slope; Local average subdivision; Spatial variability; Slope reliability